EXPOSITORY METHODS IN STUDYING ENGLISH LANGUAGE AS LEARNING STRATEGIES ABOUT GRAMMAR EXPLANATION IN STUDENTS SMAS MAMIYAI AL-ITTIHADIYAH MEDAN GRADE X AND XI - Selfitrida A. Yani (Universitas Dharmawangsa, 2023)
English language is often perceived as a difficult subject and is not liked by students, English language must be studied in school. Efforts should be made to increase the students interest to make it easier to learn English, so that the achievement of learning English can be improved. The appropriate methods include guided discovery methods and expository methods. Based on the results of the discussion and research of the data, it can be concluded that the highest score is 100Â owned by 5 students and score is 80 owned by 4 student, score is 60 owned by 1 . While the lowest score isÂ 20Â which is owned by 1 student and from the test result the students get the score 40,60,80, and 100 which is owned by 1 students. Then, it means reported question is a subject that still hard enough for student because its high percentage of error especially in changing pronouns, caused the rate of the students mastery in this subject is not too high. The students find it very difficult to pronoun because it requires understanding and mastering the grammar structure in replacing pronoun, tenses, verb and time.Keywords: discovery method, expository method.